2015
DOI: 10.1007/s00775-015-1298-7
|View full text |Cite
|
Sign up to set email alerts
|

Oxidovanadium(IV) complexes with chrysin and silibinin: anticancer activity and mechanisms of action in a human colon adenocarcinoma model

Abstract: Vanadium compounds were studied during recent years to be considered as a representative of a new class of nonplatinum metal antitumor agents in combination to its low toxicity. On the other hand, flavonoids are a wide family of polyphenolic compounds synthesized by plants that display many interesting biological effects. Since coordination of ligands to metals can improve the pharmacological properties, we report herein, for the first time, a exhaustive study of the mechanisms of action of two oxidovanadium(I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 79 publications
1
47
0
Order By: Relevance
“…However, chemical modification of chrysin has become the focus of research attention in order to resolve the abovementioned problem. 21 An oxidovanadium complex with chrysin was reported to improve chemotherapy in a colon adenocarcinoma model 22 and in an osteosarcoma model. 23 Furthermore, methoxy poly(ethylene glycol) (mPEG)-chrysin conjugates were reported to increase the encapsulation efficacy of doxorubicin and to enhance its anticancer effects.…”
Section: Introductionmentioning
confidence: 99%
“…However, chemical modification of chrysin has become the focus of research attention in order to resolve the abovementioned problem. 21 An oxidovanadium complex with chrysin was reported to improve chemotherapy in a colon adenocarcinoma model 22 and in an osteosarcoma model. 23 Furthermore, methoxy poly(ethylene glycol) (mPEG)-chrysin conjugates were reported to increase the encapsulation efficacy of doxorubicin and to enhance its anticancer effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that SIL has strong antitumor activities toward a variety of epithelium-derived tumors, such as prostate,2 colon,1 bladder,13 breast,14 ovarian,15 and lung cancers 3,4. This study analyzed the impacts of SIL on the proliferation of ACC-M cells, and the results revealed that SIL could inhibit the proliferation of ACC-M cells in time- and dose-dependent manner, particularly when treated with 160 µg/mL of SIL for 72 hours, the inhibition rate of 93% suggested that SIL had significant inhibitory activities toward ACC.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that SIL has strong antitumor activities toward a variety of epithelium-derived tumors such as colon,1 prostate,2 or lung cancer,3,4 and induction of tumor cell autophagy might be one of the mechanisms. Autophagy is a stress reaction of cells under starvation, hypoxia, and other internal or external environmental pressure conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Chrysin vanadate complex reduced to 56% the HT-29 cell survival vs. 88% in the case of cisplatin. This chrysin potentiating effect may be due to a reduction in GSH levels, one of the most important antioxidant defenses in mammals (León et al, 2015). In order to avoid gastrointestinal damage in preclinical trials, different vanadium complexes have been generated with flavonoids (Evangelou, 2002).…”
Section: Flavonoidsmentioning
confidence: 99%
“…In this combination, chrysin induces cell cycle arrest in G 2 /M transition, while silibinin induces apoptosis due to caspases activation and NF-κB inhibition (León et al, 2015). …”
Section: Flavonoidsmentioning
confidence: 99%